Analysis of the Application of Accounting Recording Based on Financial Accounting Standards for Micro, Small and Medium Entities in Small and Medium Enterprises in Baraka District, Enrekang Regency - Muh.Nur R; Muhammad Yusuf; Ismail Rasulong; Anur Achsanuddin UA (Formosa Journal of Applied Sciences, 2023)
This study aims to determine the application of accounting records based on entity, micro, small and medium financial accounting standards for small and medium enterprises in Baraka District, Enrekang Regency, using a descriptive analysis method (Descriptive Analysis Method). Descriptive analysis method is a method that provides an overview of small and medium enterprises in Baraka District, Enrekang Regency. The results of the study show that all research objects in Baraka District, namely small and medium enterprises, can already be said to be mostly using accounting recording methods, so that it can be said that these businesses have not fully implemented accounting records as required. This is due to limited human resources and inadequate accounting skills or knowledge.